A New, Robust and Applied Model for Interpolation of Huge Data - Mehdi Zamani (International Journal of Advances in Applied Sciences, 2013)
A powerful and accurate model for interpolation of data is piecewise cubic spline method.  In this model the obtained final curve consists of a series of local cubic spline curves which combine together with suitable continuity along their boundaries.  The continuity at the boundaries of each local curve is c2.  The attraction of this research is to apply cubic spline method for approximation and estimation of data.  Therefore; each local spline curve satisfies the minimization of sum of square errors along its length in addition of obtaining c2 continuity at its edges or boundaries.  Because in the local scale the approximation of any section of data by cubic spline is accurate; therefore, the presented model is applicable to any kind of data with highly nonlinear distributions.